Penyelesaian Sengketa Melalui Arbitrase dalam Sistem Hukum di Indonesia Studi Kasus Nomor Perkara : No. 44042/VI/ARB-BANI/2021 - SINGGIH, MOHAMMAD WAHYU (Peneliti.net, 2025)
Business actors frequently opt for non-litigation dispute resolution because it is considered to provide more benefits to both parties involved compared to litigation in court. One of the methods used is arbitration, which is seen as more advantageous than resolving disputes through the courts. The main benefits of arbitration are its faster process and lower costs, making it a crucial consideration for the disputing parties. Arbitration has been widely applied in Indonesia, including in the case between PT LEN Telekomunikasi Indonesia and the Ministry of Communication and Informatics, along with BAKTI, regarding the implementation of the Palapa Ring Tengah Cooperation Agreement. The dispute in this case was resolved through arbitration. In Indonesia, the arbitration process is regulated by Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, providing legal certainty for parties opting for non-litigation alternative dispute resolution.